(untitled) (Journal of Legal Studies, 2015)
The paper addresses an important problem and the frequency of teaching and learning/teaching-learning in higher education/university student, generated by the incapacity to himself selectively information conveyed through alternative sources. The theoretical approach of the course in European Union law from the dual perspective of the studies about the EU (from the perspective of Community law/EU of the European economy as well as from the perspective of the European administration, international relations and historical and cultural studies or interdisciplinary) require students to knowledge/concept related institutions entrusted with the exercise of prerogative powers in a State, who they studied/problems in previous years in fact, it is precisely this times is done or shall not become unwieldy. And last but not least not be overlooked aspects of individual differences that influence the process of learning: the way of thinking and the preferences of both factors (teachers/students) on lifelong learning, which influences the effectiveness of the approaches in the process of instruction (or multiple types of intelligence entitled, the use of information and others).